Validating criteria for identifying core concepts using many-facet rasch measurement - McLaughlin, Jacqueline E.; Angelo, Thomas A.; White, Paul J. (Frontiers in Education, 2023)
Introduction: Core concepts are foundational, discipline-based ideas considered necessary for students to learn, remember, understand, and apply. To evaluate the extent to which a concept is “core,” experts often rate concepts using various criteria, such as importance, complexity, and timeliness. However, there is a lack of validity evidence for core concepts criteria. Methods: Using a 3-facet Many-Facet Rasch Measurement (MFRM) model, we analyzed 7,558 ratings provided by 21 experts/raters for 74 pharmacology core concepts using 5 criteria measured on a 5-point scale. Results: All of the criteria had Infit or Outfit MnSq values within the expected range (0.5